Delivery Information System Web-Based Design at Bandung SPP Posts - Muntasir Muntasir; Farizal Sofyan (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
Central processing post office in Bandung is a division of PT. Pos Indonesia is in charge of all postal shipments, from the sender to the intended recipient. The main issue raised by this study is the slow process of POS SPP Bandung receiving and delivering goods.This study uses a descriptive research method, from the research that has been done, there are factors that hinder the process of receiving and delivering goods at POS SPP Bandung, as they still use a system that we consider less efficient and less efficient, so it will Interfere with the process of receiving and delivering goods. Therefore, in this paper, a Goods Delivery Information System was designed using Unified Modeling Language (UML) and implemented using PHP programming language, Framework Code version 4 and MySQL database. With this application system, it is expected that employees can make it easier and speed up the process of inputting goods into and out of the Bandung SPP Post office.